2019
DOI: 10.1038/s41598-019-44230-2
|View full text |Cite
|
Sign up to set email alerts
|

Genetic structure and forensic characteristics of Tibeto-Burman-speaking Ü-Tsang and Kham Tibetan Highlanders revealed by 27 Y-chromosomal STRs

Abstract: Culturally diverse Tibetans (Ü-Tsang, Kham and Ando) harboring a unique molecular mechanism that allows them to successfully adapt to hypoxic environments in the Qinghai-Tibet Plateau have been a subject of great interest in medical genetics, linguistics, archeology and forensic science. However, forensic characteristics and genetic variations of the Y-chromosomal 27-marker haplotype included in the Yfiler Plus system in the Ü-Tsang and Kham Tibeto-Burman-speaking Tibetans remain unexplored. Thus, we genotyped… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
13
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 49 publications
(47 reference statements)
3
13
0
Order By: Relevance
“…Our study did not simulate the Siberian ancestral component, because the original genotype data lacked northern Siberian population data. We also found that northwestern Tibetans in Qinghai Province tended to cluster with the aforementioned Uyghur and Kazakh peoples, which was consistent with the population stratification among culturally diverse Tibetans and western Eurasian affinity of Ando Tibetans in the Ganging region revealed via ancient/modern genome-wide data and Y chromosome genetic variations[22,44].Additionally, we used three TreeMix-based phylogenies to explore the phylogenetic split and potential gene flow events and to verify the patterns of population genetic relationships inferred from the PCA and ADMIXTURE. Among worldwide populations, the Medellin Colombian and Puerto Rican clusters were located between South Asian and European groups.…”
supporting
confidence: 83%
“…Our study did not simulate the Siberian ancestral component, because the original genotype data lacked northern Siberian population data. We also found that northwestern Tibetans in Qinghai Province tended to cluster with the aforementioned Uyghur and Kazakh peoples, which was consistent with the population stratification among culturally diverse Tibetans and western Eurasian affinity of Ando Tibetans in the Ganging region revealed via ancient/modern genome-wide data and Y chromosome genetic variations[22,44].Additionally, we used three TreeMix-based phylogenies to explore the phylogenetic split and potential gene flow events and to verify the patterns of population genetic relationships inferred from the PCA and ADMIXTURE. Among worldwide populations, the Medellin Colombian and Puerto Rican clusters were located between South Asian and European groups.…”
supporting
confidence: 83%
“…3C) where bordered the East China Sea, Taiwan Strait, and the South China Sea. In order to assess the degrees of differentiation of CSEH, we collected 50 778 individuals from 166 worldwide populations who belong to nine main language families [21,24,30–32,61–116]. Based on the frequencies of 27 Y‐filer Plus markers, we made a Manhattan distance‐based MDS that indicated that CSEH clustered with populations of southern China in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The PCA provides a method of visualizing the essential patterns of genetic relationships and allows us to identify and plot the major patterns within a multivariate dataset to indicate that the populations with closer geographical distances have more intimate relationships. We collected the 23 Y-STR frequency profiles of 48,162 individuals from 159 worldwide populations having nine language families within five continents ( Supplementary Table 5 ) to conduct PCA with Guangdong Hakka and She groups ( Yaju et al, 2014 ; Westen et al, 2015 ; Bai et al, 2016b ; Garcia et al, 2016 ; Jung et al, 2016 ; Pickrahn et al, 2016 ; Wang L. et al, 2016 ; Wang Y. et al, 2016 ; Guo et al, 2017 ; Iacovacci et al, 2017 ; Jun et al, 2017 ; Lacerenza et al, 2017 ; Qiang et al, 2017 ; Spolnicka et al, 2017 ; Wang M. et al, 2017 ; Zgonjanin et al, 2017 ; Zhang et al, 2017 ; Cao et al, 2018 ; Fan et al, 2018a , b , c ; Khubrani et al, 2018 ; Liu Y. et al, 2018 ; Juan et al, 2018 ; Liu Y. J. et al, 2018 ; Wang et al, 2018 , 2020 ; Zhou et al, 2018 ; D’Atanasio et al, 2019 ; Fan et al, 2019 ; He et al, 2019 ; Henry et al, 2019 ; Ip et al, 2019 ; Jankova et al, 2019 ; Kai et al, 2019 ; Lang et al, 2019 ; Liu et al, 2019 , 2020 ; Luo et al, 2019 ; Santos Stange et al, 2019 ; Tao et al, 2019a , b ; Wang C. Z. et al, 2019 ; Wang X. et al, 2019 ; Wang Y. et al, 2019 ; Wu et al, 2019 ; Xie et al, 2019 ; Yaju et al, 2019 , 2020 ; Zhabagin et al, 2019 ;…”
Section: Resultsmentioning
confidence: 99%